2009
DOI: 10.1073/pnas.0913415107
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C-γ1 is involved in signaling the activation by high NaCl of the osmoprotective transcription factor TonEBP/OREBP

Abstract: High NaCl elevates activity of the osmoprotective transcription factor TonEBP/OREBP by increasing its phosphorylation, transactivating activity, and localization to the nucleus. We investigated the possible role in this activation of phospholipase C-γ1 (PLC-γ1), which has a predicted binding site at TonEBP/OREBPphospho-Y143. We find the following. The PLC-γ1 phospholipase inhibitor U72133 inhibits nuclear localization of TonEBP/OREBP but not the increase of its transactivating activity. We conclude that, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 27 publications
1
61
0
Order By: Relevance
“…However, many reports have indicated that NFAT5 protein level is tightly regulated, particularly during differentiation and in response to hyper-osmotic stresses (Woo et al, 2000;Ferraris et al, 2002). It has been shown that NFAT5 protein level is regulated by several mechanisms involving protein stability and miRNA-mediated mRNA silencing (Dahl et al, 2001;Irarrazabal et al, 2010;Levy et al, 2010). We now report that NFAT5 protein level can also be regulated by the coupling of splicing to the NMD pathway (Figures 4, 5 and 6).…”
Section: Discussionmentioning
confidence: 51%
“…However, many reports have indicated that NFAT5 protein level is tightly regulated, particularly during differentiation and in response to hyper-osmotic stresses (Woo et al, 2000;Ferraris et al, 2002). It has been shown that NFAT5 protein level is regulated by several mechanisms involving protein stability and miRNA-mediated mRNA silencing (Dahl et al, 2001;Irarrazabal et al, 2010;Levy et al, 2010). We now report that NFAT5 protein level can also be regulated by the coupling of splicing to the NMD pathway (Figures 4, 5 and 6).…”
Section: Discussionmentioning
confidence: 51%
“…In addition, PLC-γ1 also regulates TonEBP/OREBP in a way that apparently does not involve Rac1. PLC-γ1, through its C-SH2 domain, regulates nuclear localization of TonEBP/OREBP, dependent on its lipase activity (3). This activation evidently is independent of Rac1 because Rac1 does not contribute to TonEBP/OREBP nuclear localization (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…osmotic stress | MAPK H ypertonicity (e.g., high NaCl) activates the transcription factor TonEBP/OREBP (also known as NFAT5), resulting in increased expression of osmoprotective genes (1). Hypertonicity increases TonEBP/OREBP activity by increasing its abundance (1), transactivating activity (1), nuclear localization (1), and phosphorylation (2,3). The regulatory increase of phosphorylation depends on both increased kinase activity and reduced phosphatase activity (4,5).…”
mentioning
confidence: 99%
“…Through mass spectrometry, DNA mutation, immunocytochemistry and Western analyses, NFAT5 tyrosine 143 (Y143), threonine 135 (T135), serine 155 and 158 (S155 and S158) have been identified so far as the phosphorylation sites and play a critical role in regulation of NFAT5 activity. High NaCl increases phosphorylation of NFAT5-Y143, leading to increase of NFAT5 nuclear localization in cell culture [23][24][25] , and phosphorylation of NFAT5-Y143 is increased in the normal rat renal inner medulla and the Brattleboro rat inner medulla treated with vasopressin, known to increase the renal medullary tonicity [25] . The similar Zhou X. Kinases regulate NFAT5 activity phenomena are also observed with NFAT5-T135 [26] .…”
Section: Phosphorylation Of Nfat5mentioning
confidence: 99%
“…Diacylglycerol binds a conserved C1 domain in PKC, resulting in the plasma membrane translocation and activation of the kinase [89] . High NaCl increases PLCγ1 activity [24] , diacylglycerol and total PKC activity [90] . PKC inhibitors reduce NFAT5 transcriptional activity in mIMCD3 [91] and NIH3T3 cells [84] .…”
Section: Mitogen-activated Protein Kinasesmentioning
confidence: 99%